A state of affairs of European criminology : an exploration of topics and trends through topic modelling - Daenekindt, Stijn (2020)
What is European criminology about? Through topic modelling, we investigate the content of 11,724 presentations held at the annual conferences of the European Society of Criminology, the largest and most influential professional association in Europe for those who are actively engaged in research, teaching, and/or practice in criminology, from 2001 to 2019. We extract 50 topics, and identify top contributing institutions and countries based on first author institutional affiliation. In addition, we determine the most and least influential topics in European criminology. We further explore how the prominence of topics has evolved over time and identify five topics that are increasingly being addressed and three topics that have gradually lost interest, hot and cold topics respectively. The results are discussed in light of previous research on European criminology and current debates on its epistemology